Coordinated operational planning for electric vehicles considering battery swapping and real road networks in logistics delivery service. (April 2022) - Deng, Youjun; Mu, Yunfei; Dong, Xiaohong; Wang, Xiaoyu; Zhang, Tao; Jia, Hongjie
Abstract: In the context of carbon neutrality, the electric vehicles (EVs) are increasingly used in city logistics service. To utilize EVs in the logistics delivery service in a cost-effective manner, this paper proposes a coordinated operational planning method for EVs considering the real road networks and battery swapping for EVs. Specifically, utilizing the EVs parked in the depot to discharge to power the depot or feed to the grid for an arbitrage, this paper is to minimize the sum of transportation cost and energy cost by determining the optimal number of EVs assigned to delivery goods and their driving route, as well as the charge–discharge operation decisions of all EVs including those without a delivery assignment and those returning to the depot after completing delivery. In simulation study, the effectiveness of the proposed methods is finally validated.